Metonymy in Words Specific to the Noun Phrase - Rohila Akramovna , Suvonova (International Journal of Psychosocial Rehabilitation, 2020)
One of the most common and interesting fields of linguistics is that its methodology is rich in artistic means of representation, and its role in the mechanism of creation of a work and in enhancing its artistry is incomparable. The meaning of a word and the changes that take place in it in the creation of a work of art show its complexity. One of the artistic means that defines and creates the development of word meaning is metonymy. Metonymy is actively involved in the semantic changes that occur in all independently meaningful words—nouns, adjectives, numbers, rhymes, forms, and verbs. It has therefore been shown to fully reveal its lingvo-lubi character and is more common, especially in words peculiar to the noun phrase. This scientific article is also devoted to the specificity of metonymy in the category of nouns and the features of its expression and selected and analyzed original examples from works of art and poetry. As a result of the observations, the translucent meanings of metonymy were highlighted as a linguistic and speech phenomenon that is multifaceted and has a wide range of semantic development in words specific to the noun phrase.